2014
DOI: 10.1109/tdei.2014.004306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface fluorination on space charge behavior in multilayered polyimide films

Abstract: In recent years, the multilayered polyimide films have been widely used in flexible PrintCircuit Board in order to reduce the thickness of the combination of the flexible PrintCircuit Board. The existence of space charge as a main reason for dielectric breakdown, has a great effect on breakdown characteristic. So it is important to study the space charge characteristics of the multilayered polyimide films. Fluorination can change the chemical component in surface layer of polymers and therefore can influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For example, various kind of plasma treatments of cellulose paper have been utilized to enhance their hydrophobicity [18][19][20]. As one of the most commonly used surface modification method, gas-phase fluorination has already been used to modify the surface charge and space charge dynamics of polymer such as polyethylene, polypropylene, polyimide and epoxy resin [21][22][23][24]. Previous studies also show that the surface charge dissipation of oil-impregnated cellulose insulation paper under DC and pulse voltage could be accelerated by gas-phase fluorination [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, various kind of plasma treatments of cellulose paper have been utilized to enhance their hydrophobicity [18][19][20]. As one of the most commonly used surface modification method, gas-phase fluorination has already been used to modify the surface charge and space charge dynamics of polymer such as polyethylene, polypropylene, polyimide and epoxy resin [21][22][23][24]. Previous studies also show that the surface charge dissipation of oil-impregnated cellulose insulation paper under DC and pulse voltage could be accelerated by gas-phase fluorination [25].…”
Section: Introductionmentioning
confidence: 99%
“…The trap become shallower, accelerating the transport and reducing the charge accumulation [97–100, 102, 103], including positive and negative charges [99]. Diminishing charge accumulation is contributed to weaken the electric field distortion on the surface, which improves the surface flashover voltage.…”
Section: Materials Modificationmentioning
confidence: 99%
“…For example, An et al [20,21] indicated that surface fluorination of PE has a significant influence on the charge injection and accumulation. Du et al [22,23] found that surface fluorination is an effective method for modulating the electrical properties and restraining the surface charge and space charge accumulation of the PI film.…”
Section: Introductionmentioning
confidence: 99%